Microleakage of two different posterior composites and a high-viscosity glass-ionomer cement: An in vitro study - Celenk, Sema; Ayna, Buket; Günay, Ayşe; Ataş, Osman (My University, 2022)
Aim: Using AutoCAD, we examined the microleakage of permanent molars in Class I restorations using a conventional posterior composite resin, a bulk-fill composite resin, and a high-viscosity glass-ionomer cement (HVGIC). Methodology: In total, 33 extracted noncarious third molars were used. Class I cavities were prepared. The teeth were randomly divided into three groups of 11 teeth each, as follows: Group A (Filtek Z550), Group B (Filtek Bulk-Fill Posterior Restorative), and Group C (EQUIA Fil). All specimens were stored for 24 h at 37 °C in distilled water. The teeth were thermocycled 1,000 times between 5 ± 2?C and 55 ± 2°C prior to immersion in 0.5% basic fuchsin for 24 h. Two mesiodistal cuts of each tooth were photographed under a stereomicroscope equipped with a digital camera. The dye-infiltrated surface area was measured. Results: Statistical evaluations were performed by one-way analysis of variance [ANOVA]. One-way ANOVA showed no significant difference between the three groups in microleakage (P = 0.07). However, the lowest microleakage ratio was seen in Group C (EQUIA Fil). Similar results were obtained with all tested materials, but the lowest microleakage rate was obtained with EQUIA Fil (Group C). Conclusion: In this study, the tested materials were not completely successful in eliminating microleakage, although the lowest microleakage rate was obtained with EQUIA Fil.
Keywords: Diş Hekimliği